USING AUDIO-LINGUAL METHOD TO IMPROVE THE STUDENTS’ SPEAKING SKILL - Eda Maaliah; Yulius Harry Widodo; Muhyiddin Aziz (Jurnal Bahasa Inggris Terapan, 2017)
Language teachers play an important roles on teaching and   learning   process,   choosing   the   methods,   and designing the goal of the study. All their targets are based on how well they collaborate the methods and designs through the experiences and knowledge they have during the  process   of  teaching  and   learning.   Audio-lingual method was chosen to know the effectiveness, advantages, disadvantages, strenghts, and weaknesses   in improving the speaking skill of the fifth grade students of elementary school. The qualitative and quantitative data were used in this research. Qualitative data were taken from the scores of the pre-test and all cycles. The quantitative data were taken through the observation, interview, and questionnaire. Based on the discussions and conclusions, audio-lingual method is recommended to improve the speaking skill of elementary students.Key words: audio-lingual method, speaking skill, teaching learning process